KIR3DL05 and KIR3DS02 Recognition of a Nonclassical MHC Class I Molecule in the Rhesus Macaque Implicated in Pregnancy Success - Nicholas, Rachel E.; Sandstrom, Kjell; Anderson, Jennifer L.; Smith, Willow R.; Wetzel, Molly; Banerjee, Priyankana; Janaka, Sanath Kumar; Evans, David T. (Frontiers in Immunology, 2022)
Knowledge of the MHC class I ligands of rhesus macaque killer-cell Ig-like receptors (KIRs) is fundamental to understanding the role of natural killer (NK) cells in this species as a nonhuman primate model for infectious diseases, transplantation and reproductive biology. We previously identified Mamu-AG as a ligand for KIR3DL05. Mamu-AG is a nonclassical MHC class I molecule that is expressed at the maternal-fetal interface of the placenta in rhesus macaques similar to HLA-G in humans. Although Mamu-AG and HLA-G share similar molecular features, including limited polymorphism and a short cytoplasmic tail, Mamu-AG is considerably more polymorphic. To determine which allotypes of Mamu-AG serve as ligands for KIR3DL05, we tested reporter cell lines expressing five different alleles of KIR3DL05 (KIR3DL05*001, KIR3DL05*004, KIR3DL05*005, KIR3DL05*008 and KIR3DL05*X) for responses to target cells expressing eight different alleles of Mamu-AG. All five allotypes of KIR3DL05 responded to Mamu-AG2*01:01, two exhibited dominant responses to Mamu-AG1*05:01, and three had low but detectable responses to Mamu-AG3*03:01, -AG3*03:02, -AG3*03:03 and -AG3*03:04. Since KIR3DL05*X is the product of recombination between KIR3DL05 and KIR3DS02, we also tested an allotype of KIR3DS02 (KIR3DS02*004) and found that this activating KIR also recognizes Mamu-AG2*01:01. Additional analysis of Mamu-AG variants with single amino acid substitutions identified residues in the 1-domain essential for recognition by KIR3DL05. These results reveal variation in KIR3DL05 and KIR3DS02 responses to Mamu-AG and define Mamu-AG polymorphisms that differentially affect KIR recognition.